Auditoría de gestión al colegio particular continental, ubicado en el cantón Latacunga, provincia de Cotopaxi en el período enero – diciembre del 2014 - Benavides Huertas, Patricia Victoria (2015)
The research work has as general objetive to analyze each of the designated activities in the Administrative, Human Resources and Financial Departments; in order to determine the degree of efficiency, efficacy, and economy, in the use of available resources that were developed ¨Continental¨ Private School in Latacunga city during the academic cycle 2014. The performance audit allowed to examine the operations carried up in this period, with the purpose of evaluating the financial and administrative development of the High school, so through this auditory, it could issue recommendations that allow to make the best decisions for the institution. One of the main objetives of the performance audit within the entity was to determine the degree of compliance of the desired goals and objectives; it could evaluate the performance that took each of the members that make up the institution. Moreover….